(3GdEOGQI hGdJNWjW GdESJQGJjLj (B/s - (3YOhf, fGUQ OGOjs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2017)
(3GdESJQGJjLjI HGdeDSSI GdEbJUGOjI(B- (3GdESJQGJjLjI hSjGSI GdeDSSI(B- (3GdGSJQGJjLjI hGdGgOGa(B- (3GdJNWjW hCfhGY fXGe GdJNWjW GdCSJQGJjLj(B- (3GdJNWjW GdESJQGJjLj aj GdeDSSI GdEbJUGOjI GdYehejI(B- (3GdJMdjd GdESJQGJjLj HGdWQb GdMOjKI(B- (3EOGQI hGJNGP GdbQGQGJ aj GdeDSSII GdEbJUGOjI(B- (3GdEOGQI hfXGe eYdheGJ GdJSjjQ(B- (3GdJNWjW GdESJQGJjLj aj GdeDSSI GdLRGFQjI NdGd GdKeGfjfGJ aj GbJUGO GdShb(B.s
(3GdeQGLY U(B.185s
Keywords: (3GdEOGQIs; (3GdJNWjW GdESJQGJjLjs